Screening of Synergistic Interactions of Epigallocatechin-3-gallate with Antiangiogenic and Antitumor Compounds - Rodríguez-Quesada, Ana María; Medina-Torres, Miguel Ángel; García-Vilas García, Javier Alejandro (Elsevier, 2016)
Purpose: To screen for possible synergistic interactions of epigallocatechin-3-gallate (EGCG) with a selection of 10 anti-angiogenic or anti-tumor compounds on the survival of endothelial and tumor cells. Methods: Human HMEC endothelial and MDA-MB231 breast cancer cells were treated with different concentrations of EGCG and the 10 tested compounds either as single agents or in paired combinations with EGCG for 3 days and final survival of cells was determined by the MTT assay. IC50 values, sensitization factors and combination indexes were calculated. Results; IC50 values of 140±2 and 45±6 μM were determined for EGCG-treated endothelial and tumor cells, respectively. IC50 values for all tested compounds were within the micromolar and the submillimolar range. The values of the sensitization factor increased and those of the combination index decreased for paired combinations of EGCG with 4-methylumbelliferone. The opposite was true for the combination of EGCG with vitamin D3. Other tested combinations did not exhibit a clear monotonic effect but rather a biphasic behaviour. Conclusion: Combinations of EGCG and 4-methylumbelliferone synergistically decrease endothelial and tumor cell survival. In contrast, the presence of EGCG antagonizes with the antiproliferative effect exerted by vitamin D3 on endothelial and tumor cells.
This is the accepted manuscript of the article that finally was published in Synergy with DOI: 10.1016/j.synres.2016.05.001
Keywords: Cancer; EGCG; MTT assay; Angiogenesis; Synergy